Theory and empirics of horizontal and spatial integration of local communal services - Katalin Czako; Veronika Poreisz (European Regional Science Association (ERSA), 2013)
There are three parts of our paper. Firstly, it gives an overview about the goals and factors which affect the integration of local communal services. Horizontal integration means joining the various individual service providers, such as water supply and sewage, communal waste, district heating, streetcleaning, public transportation companies. Spatial integration means joining the service providers of neighbouring communities. In recent years several examples can be observed for both types of integration in Hungary. Three main factors behind this trend will be discussed in detail: economies of scope argument, economies of scale argument and managerial power and prestige argument. According to the economies of scope argument, local service providers use similar physical assets (such as vehicles, office buildings, maintenance tools and so on) and similar skills and organizations. Joining of the respective customer bases brings synergies in the management of users (metering, billing, call centres and so on), and in administration costs. Bigger organizations may be in a better position in order to raise the funds required for financing their projected investments also. The economies of scale argument lies behind the spatial extension of the providers of the same service. However, spatial extension leads to the increasing cost of spatial interactions among the various sites of companies also which effect can overweight the potential cost reduction due to the increasing return. Horizontal and spatial integration can be driven also by managerial attitude towards empire building. The second part of the paper presents a short survey about the previous controversial empirical findings of the integration of local communal services in various countries. In the third part our own empirical research is presented, firstly as a case study about the integration of communal waste, district heating, real estate services and other general services in the Western Hungarian town of Gy\~or (which has about 130 thousand inhabitants) and secondly a comparative study about six other Hungarian towns (with similar size). Our results suggest a balanced view: cost efficiency argument cannot be verified in administrative activities, neither in horizontal nor in spatial integration, but there is slight cost efficiency in physical activities. The changing organizational structure and the joint human resource management have both advantages and disadvantages.
Keywords: R5; R11; L23; L97; H54; 330; local communal services; horizontal integration; spatial integration; organizational structure